Effectiveness of Mediterranean Diet pyramid on diabetic control and cardiovascular risk modification among patients with Type 2 Diabetes Mellitus at a hospital in Muscat, Oman - Al-Aufi, Najwa Salim Khalfan Nasser (2022)
Adoption of the Mediterranean Diet (MedDiet) has been shown to be effective on glycaemic control and decrease cardiovascular risk among individuals with diabetes mellitus in different populations. However, little compelling evidence is available on the effectiveness of MedDiet among Omanis. The general objective of this study is to determine the effectiveness of the Mediterranean Diet on glycaemic control and cardiovascular risk among type 2 diabetes patients in Muscat, Oman. This wait-list, open-labelled, randomized control trial aimed to assess if the provision of a 6 month MedDiet intervention is effective on cardiovascular risks and diabetic control. A total of 134 patients with Type 2 Diabetes Mellitus (T2DM) from the Nutrition Clinic of National Diabetes and Endocrine Centre at the Royal Hospital, Muscat, Oman was recruited and assigned into standard low-calorie diet control (1200-1500 calorie per day for women and 1500-1800 calories per day for men) (n=73) or MedDiet (n=61) group. Follow-up assessments and data collection were conducted during baseline, three and six months after the intervention. All data was analysed using SPSS version 26, with mixed model ANOVA was used to delineate the effectiveness of Mediterranean Diet intervention as compared to standard low-calorie diet. At baseline, average age of study participants was 44 years old. A higher proportion of them were female (56.3%), married (66.7%), have above primary education (69.4%), working (54.0%) and lower-income (< 800 rials; 50.8%). Total calories, carbohydrates, and fats intake were comparable between the two groups, while participants in the control group had significantly higher protein intake (17.5±4.5g vs. 15.5±3.7, t = 2.660, p = 0.009) compared to intervention group. Trans fat intake was significantly higher in intervention group (2.3±2.4 g vs. 1.3±1.7g, t = -2.501, p=0.014), while cholesterol intake was significantly higher in control group (270.1±160.8mg vs. 197.7±133.7mg, t = 2.726, p =0.007). Approximately three-quarters of the participants had poor adherence to the MedDiet, especially in intervention group (88.1% vs. 62.7%; χ2 = 10.72, p = 0.001). There was a significant difference in the mean score of the MedDiet between study groups (control: 4.82 ± 2.18 vs. intervention: 3.78 ± 1.40; t =3.217, p =0.002). For the food groups, the cohesion for the usage of olive oil as the main cooking or culinary fat (0.10 ± 0.31 vs. 0.02 ± 0.13; t= 2.120, p = 0.045), commercial sweets or pastries (not homemade) (0.49 ± 0.50 vs. 0.31 ± 0.46; t = 2.173, p=0.032), vegetables (0.33 ± 0.47 vs. 0.08 ± 0.28; t = 3.561, p=0.001) and butter, margarine or cream (0.10 ± 0.31 vs. 0.01 ± 0.13; t= 2.120, p= 0.037) were higher among the control group compared to the intervention group. There were comparable self-perceived to healthy eating between the two groups such as personal and environmental barriers (11.40 ±1.71 vs. 11.42 ± 1.85; χ2= 0.065, p= -0.948), social and environmental barriers (7.70 ±1.24 vs. 8.12 ±1.53; χ2= 1.686, p= -0.094) and level of perceived barrier to healthy eating (Low (<17); 5(7.5) vs. 7(11.9); χ2= 3.689, p = 0.158), Moderate (17 – 22); 60(89.6) vs. 46(78.0), High (> 22); 2(3.0) vs. 6(10.2)). Moreover, the control participants have higher self-efficacy to healthy eating and diabetes management (19.91±2.53 vs. 19.49±2.38; t= 0.953, p= 0.343) compared to the intervention group. About 6% of the study participants have a high perceived barrier to healthy eating while almost 70% have low self-efficacy to healthy eating and diabetes management. There were 26% of the participants had low physical activity and 30% have a risk of dozing off. The control and intervention participants have comparable vigorous physical activity (65.07±143.69 vs. 48.14±139.71; t= 0.669, p = 0.505), moderate physical activity (113.13±106.66 vs. 101.69±111.50; t= 0.588, p= 0.558), walking (740.28±240.82 vs. 678.73±179.48; t = 1.608, p= 0.110) and total intensity of physical activity (918.49±377.93 vs. 828.57±307.63; t= 1.452, p= 0.149). With regards to daytime sleepiness, male participants from the intervention group and female participants from the control group have higher daytime sleepiness. The anthropometry parameters namely weight (108.9±23.6 kg vs. 118.1±23.2 kg; t= -2.195, p = 0.030) and Body Mass Index (41.6±7.9 kg/m2 vs. 44.6±7.7 kg/m2; t= -2.182, p= 0.031) were higher among the intervention participants. Dietary phosphorus was inversely associated with HbA1c concentration (p= 0.023) among the study participants, while increased in calcium intake was associated with higher concentration of HbA1c (p=0.007). Higher score in barriers to healthy eating and self-efficacy were associated with higher concentration of HbA1c (p=0.008 vs. p < 0.001). Higher fasting blood glucose and LDL cholesterol were also associated with increased HbA1c among the study participants (p= 0.003 vs. p= 0.001). There was no significant different in the mean or distribution of the metabolite traits between the intervention and control participants. On the other hand, there were 80-90% of the participants had sub-optimal glycaemic control, hypercholesterolemia, hypertriglyceridemia, and elevated low-density lipoprotein, with 77% of them had metabolic syndrome. Obesity was prevalent with about 65% were either severely or morbidly obese with 80% had central obesity. After 6 months intervention, adherence to MedDiet had increased significantly over time in the intervention group, with mean changes were significantly higher between baseline and 6 months follow-up. Using repeated measure ANOVA, MedDiet intervention has small to moderate but significant effects towards reducing metabolic profiles (additional reduction of 4.88%, 13.28%, 14.89% and 23.18% for total cholesterol, HbA1c, triglycerides and fasting blood glucose, respectively) and anthropometrics parameters (additional reduction of 12.07%, 12.01% and 4.77% for body weight, body mass index and waist circumference, respectively). In addition, there was significant increase in physical activity intensity but lesser daytime sleepiness in the intervention participants as compared to their control counterparts. The current study revealed that carefully plan nutritional education emphasizing MedDiet was effective and superseded the conventional nutrition counselling in the improvement of metabolic control (glycaemic control and reduction of cardiovascular risk), dietary intake, psychosocial factors, daytime sleepiness, physical activity of T2DM patients. The current educational module can be incorporated in the existing diabetic control program for optimising metabolic control of T2DM patients from non-Mediterranean countries or populations like Oman.